2017
DOI: 10.1183/13993003.00265-2017
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus species/genotypes and interferon-λ: subtypes, receptor and polymorphisms – missing pieces of the puzzle of childhood asthma?

Abstract: We agree about the importance of rhinovirus-C in asthma pathogenesis. In fact, rhinovirus genotyping is currently underway and the results of all Predicta cohorts will be published in a separate manuscript. Moreover, we agree with C. Scagnolari and co-workers that IFN-λ and IFN-λR distribution in the airways are relevant to asthma, so they require separate study. Moreover, beside epithelial cells, we have recently reported that IFN-λR is also expressed in pulmonary CD11c+ dendritic cells [1]. In our original m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Two cohorts of preschool children (age 4-6 years) with and without asthma were analyzed. The recruitment of the subjects, inclusion and exclusion criteria as well as the timescale for clinical visits and data collection were exactly described recently 1,2,5,6 along with the clinical aspects and characteristics and reported in other form in Tables 1 and 2. For gene expression analysis, we isolated messenger RNA (mRNA) from total blood cells of the children as previously described and performed quantitative real-time polymerase chain reaction (PCR) as described below. 1 The levels of C-reactive-protein (CRP) in the serum samples of the children were measured by turbidimetry on a Roche Integra 800 Analyzer (CRPL2 reagent, limit of detection 1.0 mg/L, interday CV 1.4% [8.1 mg/L]; Roche Diagnostics, Basel, Switzerland).…”
Section: Human Study Predictamentioning
confidence: 99%
See 4 more Smart Citations
“…Two cohorts of preschool children (age 4-6 years) with and without asthma were analyzed. The recruitment of the subjects, inclusion and exclusion criteria as well as the timescale for clinical visits and data collection were exactly described recently 1,2,5,6 along with the clinical aspects and characteristics and reported in other form in Tables 1 and 2. For gene expression analysis, we isolated messenger RNA (mRNA) from total blood cells of the children as previously described and performed quantitative real-time polymerase chain reaction (PCR) as described below. 1 The levels of C-reactive-protein (CRP) in the serum samples of the children were measured by turbidimetry on a Roche Integra 800 Analyzer (CRPL2 reagent, limit of detection 1.0 mg/L, interday CV 1.4% [8.1 mg/L]; Roche Diagnostics, Basel, Switzerland).…”
Section: Human Study Predictamentioning
confidence: 99%
“…We recently described that acute in vitro infection of PBMCs from preschool children with and without asthma with RV, a single-stranded RNA picornavirus, is associated with the upregulation of IFN-regulated genes like STAT1, STAT2, and IFN regulatory factor 1. 1,2 Moreover, paradoxically, IFNγ upregulates also PD-L1, a factor involved in silencing/ exhausting of activated T cells by ligating PD1 on the surface of T cells. 10 Consistently, we found that acute RV infection ex vivo induced PD-L1 and CTLA4 in the PBMCs of asthmatic children.…”
Section: Pd-l1 Is Induced In Blood Cells Of Preschool Asthmatic Chimentioning
confidence: 99%
See 3 more Smart Citations